IgG4 Related Lung Disease. (30th March 2016) - Patel, Mihir; Kumar, Beena; Diep, My Linh; Nandurkar, Deepali
Abstract : IgG4 related disease is a poorly understood immune mediated condition. Lung involvement is rare and difficult to diagnose and can mimic primary lung malignancy on imaging. A patient who was found to have an incidental lung lesion with risk factors for primary pulmonary malignancy is reported.